The Effectiveness of Learning Writing Expository Texts Containing Disaster Mitigation using Video Based on the Creativity Level of Class X Students, in Ile Ape, Lembata, East Nusa Tenggara - Lenga, Klemens Maksianus; Zulaeha, Ida; Wagiran, Wagiran (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Expository texts writing is important skill in stimulating students' abilities for expressing various thoughts, ideas, opinions, facts. Also, can improve students' abilities in using proper Indonesian. The effectiveness of learning expository texts writing can be increased through the selection of appropriate learning media. Therefore, this study aims to analyze the effectiveness of learning writing expository texts contained disaster mitigation using video based on the creativity level of students in class X. The level of creativity of students is a moderate variable that can affect learning outcomes. This experimental research used a quasi-experimental factory design. Data collection was carried out through pre-test and post-test. Data analysis used paired sample t-test and ANOVA. The results of this study prove the influence of the use of learning media on student learning outcomes. Thus, it can be concluded that the use of video media is proven to be effective in improving the learning outcomes of writing exposition texts.